LEGITIMISING THE ILLEGITIMATE : EXTENDING INTERPRETATION BEYOND REALITY. THE SHRIMP FAIRYTALE AND ITS IMPLICATIONS - Martin, Mervyn (UI Scholars Hub, 2016)
The challenges of liberalization of international trade; Firstly was the realization that in the past there was a tendency to be satisfied with sweeping, unspecific statements on best principles, which always led to often a meaningless outcome without hard and fast commitments. The second was their episodic character. The notion of dispute settlement involves conflicting assertions as to the rights and obligations of the parties involved. Disputes arise from freely entered relationships between parties that create expectations as to their future conduct. there existed a three-pronged objective of the negotiating plan indicated from the Negotiating Group on Dispute Settlement for the UR negotiating process. The use of interpretory aids may become necessary when there is ambiguity in the text of the agreement. The observations indicate that that the Trade Stakeholder model is flawed in some agreement and the increasing influence of this model can be seen from an observation of similar-type cases over the years. Consistency on attempts to manipulate negotiated rights and obligation through “extended” approach became clear in Shrimp. Current slant of DSC decisions should continue to be applied.